Mathematics Communication Skills Using E-Learning-Based Problem Based Learning In Term Of Learning Styles - Disty, Indi Rifkiana; walid, Walid; Hartono, Hartono (Universitas Negeri Semarang, 2021)
This research aims to determine mathematics communication skill patterns through an E-learning-based Problem Based Learning model reviewed from learning styles. This mixed-method research applied a sequential explanatory design. The subjects consisted of 32 AMNI Maritime University Semarang students, from the transport management department, based on three learning styles: visual, auditory, and kinesthetic. The data were collected using a mathematics communication skill test, learning style questionnaire, documentation, and interview. The findings showed that visual and auditory typed students' mathematics communication skills had reached accurate writing skills. They could also conclude and answer the given problems accurately. On the other hand, the visual and kinesthetic typed students could state the daily problems by writing the information. However, they were less capable of writing them into mathematics notation. The students with auditory and kinesthetic learning styles could not completely illustrate the given problems.